Identification of contribution and lacks of the ecodesign education to the achievement of sustainability issues by analyzing the French education system. Issue 1 (29th February 2020) - Perpignan, Catherine; Robin, Vincent; Baouch, Yacine; Eynard, Benoit
Abstract: The sustainability concept is becoming ingrained in the international engineering community. The next generation of engineers has to be trained to appreciate economic, environmental, and societal impacts of its decisions, with an international perspective and at a local and global scale. The aim of this paper is to contribute to identifying the strengths and limits of current sustainability education practices to will be able to improve future decision-makers' and product designers' training. The first step of our research concerns the identification of knowledge, skills, attitudes, and values associated with sustainability and ecodesign to highlight what kind of engineers' competencies for sustainability have to be trained. Based on this identification, we examine the French education system from secondary school to university to study sustainability and ecodesign integration in different technological French curricula and practices. The objective is to estimate the effective place of sustainable development and ecodesign in the technological training courses. We analyze programs and complete our approach by observing teachers in their classrooms or by conducting interviews. Even if concepts, knowledge and skills related to ecodesign appear in many different programs, our study emphasizes that there is not a continuum between pre-secondary school, high school, and university. As a consequence, teachers have difficulties to understand the aims and the coherence of the program, and students are not really comfortable with the issues of sustainability and ecodesign. We propose to improve programs and practices by developing multidisciplinary curricula covering most of the sustainable issues and integrating best practices of international universities.